The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1074/jbc.m801238200
|View full text |Cite
|
Sign up to set email alerts
|

Role for DNA Polymerase κ in the Processing of N2-N2-Guanine Interstrand Cross-links

Abstract: Although there exists compelling genetic evidence for a homologous recombination-independent pathway for repair of interstrand cross-links (ICLs) involving translesion synthesis (TLS), biochemical support for this model is lacking. To identify DNA polymerases that may function in TLS past ICLs, oligodeoxynucleotides were synthesized containing site-specific ICLs in which the linkage was between N 2 -guanines, similar to crosslinks formed by mitomycin C and enals. Here, data are presented that mammalian cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
187
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(197 citation statements)
references
References 48 publications
10
187
0
Order By: Relevance
“…Pol k was shown to catalyze accurate bypass of N 2 -N 2 -guanine ICL in vitro, and Pol k-depleted cells show chromosome instability and decreased survival following MMC exposure (Minko et al 2008). The A family Pol u (POLQ) can extend DNA from mismatched bases in vitro (Seki and Wood 2008).…”
Section: Tls Polymerases In Icl Repairmentioning
confidence: 99%
“…Pol k was shown to catalyze accurate bypass of N 2 -N 2 -guanine ICL in vitro, and Pol k-depleted cells show chromosome instability and decreased survival following MMC exposure (Minko et al 2008). The A family Pol u (POLQ) can extend DNA from mismatched bases in vitro (Seki and Wood 2008).…”
Section: Tls Polymerases In Icl Repairmentioning
confidence: 99%
“…1A) containing various model acrolein-mediated N 2 -N 2 -guanine cross-links (see Fig. 1B) were synthesized and purified as previously described (6) Proteins-E. coli pol II and pol IV were purified as described previously (9,10).…”
Section: Generation Of Oligodeoxynucleotides Containing Site-specificmentioning
confidence: 99%
“…These investigations revealed that pol was able to catalyze bypass of ICL lesions in which the nucleotides 3Ј to the lesion had been removed (6).…”
mentioning
confidence: 99%
“…Interstrand cross-links create complete obstructions of these fundamental DNA metabolic processes, leading to potent genotoxicity. Importantly, ICLs can arise from exogenous agents such as the anticancer drugs cisplatin and mitomycin C (MMC) and endogenous sources in the form of by-products of metabolic processes (4). In general, these agents also form intrastrand cross-links (5).…”
mentioning
confidence: 99%